2015
DOI: 10.24127/ajpm.v4i1.67
|View full text |Cite
|
Sign up to set email alerts
|

Kesalahan Siswa Sekolah Dasar Dalam Merepresentasikan Pecahan Pada Garis Bilangan

Abstract: Fraction is one of the complex material in elementary school. This study aims to describe how students represent fractions on a number line, and describes the mistakes made in the students represent fractions on the number line. This research is qualitative. Subjects in this study there are two students class V of SDN Tamping Mojo II. The data collection method using a task-based interviews. Instruments in this study is the researchers themselves and supporting instruments is a task sheet and interview guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
1
5
0
13
Order By: Relevance
“…Based on the results of students' answers and interviews with students and teachers, it can be concluded that there are many students committed representation errors including visual, symbolic and verbal representation. This is in line with results of the study conducted by Suryowati (2015) reported that many students have not understood how to represent the reallife problem into mathematics problem. Students have difficulty in understanding the word problem because students are still confused and not able to interpret the sentences presented.…”
Section: The Factors Influencing Students' Mathematical Representationsupporting
confidence: 90%
“…Based on the results of students' answers and interviews with students and teachers, it can be concluded that there are many students committed representation errors including visual, symbolic and verbal representation. This is in line with results of the study conducted by Suryowati (2015) reported that many students have not understood how to represent the reallife problem into mathematics problem. Students have difficulty in understanding the word problem because students are still confused and not able to interpret the sentences presented.…”
Section: The Factors Influencing Students' Mathematical Representationsupporting
confidence: 90%
“…Legi (2008) menyatakan bahwa siswa dengan kemampuan rendah, kesulitan dalam menciptakan dan menggunakan representasi simbolik dan gambar. Selain itu, Suryowati (2015) juga mengungkapkan bahwa siswa masih belum memahami bagaimana merepresentasikan masalah dunia nyata ke dalam masalah matematika yang representatif. Dua penelitian tersebut (Legi, 2008;Suryowati, 2015) merekomendasikan upaya yang dapat dilakukan guru agar siswa memiliki kemampuan representasi dengan memilih dan menggunakan pendekatan pembelajaran yang tepat, sehingga proses pembelajaran berlangsung optimal dan mampu mengembangkan kemampuan representasi matematis.…”
Section: A Pendahuluanunclassified
“…They also merely focusing on the figure without any attention on the available information. In addition, Suryowati (2015) revealed that students have not been able to interpret real-world problems into mathematical representation problems.…”
Section: Introductionmentioning
confidence: 99%